Managing the airway catastrophe: longitudinal simulation-based curriculum to teach airway management - Lily H. P. Nguyen; Ilana Bank; Rachel Fisher; Marco Mascarella; Meredith Young (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background A longitudinal curriculum was developed in conjunction with anesthesiologists, otolaryngologists, emergency physicians and experts in medical simulation and education. Methods Residents participated in four different simulation-based training modules using animal models, cadavers, task trainers, and crisis scenarios using high fidelity manikins. Scenarios were based on various clinical settings (i.e. emergency room, operating room) and were followed by video-assisted structured debriefings. Participants completed both a self-assessment questionnaire and an exit survey using five-point Likert scales. Results 31 otolaryngology residents participated in the curriculum. Residents reported simulation training significantly improved technical skills such as tracheostomy, cricothyroidotomy and pediatric intubation (p < 0.05 for all). Non-technical skills, including communication, delegation and management were significantly improved on post-test surveys in simulated crisis scenarios (p < 0.05 for all). 90 (28/31) of participants found simulations to be very realistic. Junior residents placed increased value on didactic teaching and procedural skills, while senior residents on crisis scenarios. Survey results indicated that > 90% (28/31) of participants found the modules of the curriculum to be useful and would recommend them to others. Conclusion A longitudinal simulation-based medical curriculum can be an effective method to teach airway management and teamwork skills to otolaryngology residents.